Psychometric Characteristics of Sustainable Behaviour Metric for Middle School Students - Al-Shahrani, Fatima Abdullah; Al-Ghamdi, Nawal Gram Allah (Journal of Educational and Psychological Sciences, 2024)
The aim of this study was to develop a Sustainable Behavior Scale for middle school students and to verify its psychometric properties. The study followed an analytical descriptive approach, by reviewing previous studies and reports, in addition to analyzing the electronic questionnaire distributed to a number of middle school students, totaling 175 students, whose ages ranged from approximately 12 to 15 years old. The sample participants were randomly selected from middle schools in Tabuk. To assess the psychometric properties of the scale, validity and reliability were examined. To verify the validity of the scale, both face validity, convergent validity, and discriminant validity of the items were used, along with confirmatory factor analysis. Additionally, the reliability of the scale was examined through McDonald’s Omega and split-half reliability. The results of the current study confirmed the quality of the psychometric properties of the Sustainable Behavior Scale and its suitability for use with a sample of middle school students in the Saudi community. It is anticipated that the scale will facilitate research in this field.